2006
DOI: 10.1089/met.2006.4.179
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone Restores Endothelial Function in Patients with Type 2 Diabetes Treated with Insulin

Abstract: The primary aim of this study was to evaluate the effect of pioglitazone on endothelial function, as assessed by flow-mediated dilatation (FMD) nitroglycerine-induced dilatation (NID) in patients with type 2 diabetes mellitus treated with insulin. A randomized double-blind placebo-controlled trial involved 20 patients with insulin-treated type 2 diabetes. Patients received either pioglitazone 30 mg or placebo for 4 months. FMD, NID, and HbA1c were measured before and after 4 months of treatment. HbA1c decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 22 publications
0
29
0
1
Order By: Relevance
“…Of these, eight fulfilled the inclusion criteria and compared pioglitazone plus insulin with insulin. [231][232][233][234][235][236][237][238] One compared pioglitazone plus insulin with pioglitazone. The remaining trials were excluded because they did not examine the comparison of interest, and one was the uncontrolled extension of a trial that seemed relevant but could not be identified (shown in Table 24).…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, eight fulfilled the inclusion criteria and compared pioglitazone plus insulin with insulin. [231][232][233][234][235][236][237][238] One compared pioglitazone plus insulin with pioglitazone. The remaining trials were excluded because they did not examine the comparison of interest, and one was the uncontrolled extension of a trial that seemed relevant but could not be identified (shown in Table 24).…”
Section: Search Resultsmentioning
confidence: 99%
“…For four 231,233,234,238 of the eight trials, randomisation was adequate, whereas for the remaining four trials the randomisation procedure was not reported or unclear. Three trials 231,233,238 had adequate allocation concealment, whereas the rest of the trials did not report on allocation concealment.…”
Section: Quality Of Studiesinsulin + Pioglitazone Vs Insulinmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8]10,11 This was the first study to evaluate the effect of rosiglitazone on endothelium in patients with advanced diabetes treated with insulin, although previous studies using pioglitazone in addition to insulin treatment have also shown improvement in endothelial function. 9,12 The low-dose regimen of rosiglitazone used in this study (i.e. 4 mg/day) has been previously associated with improved endothelial function only in non-diabetic populations.…”
Section: Discussionmentioning
confidence: 93%
“…Положительное влияние метформина на функцию эндотелия было от-мечено в клинических условиях у женщин, стра-дающих поликистозом яичников, что связыва-лось с уменьшением уровня тестостерона и 17-гидроксипрогестерона [48]. При наблюдении больных СД 2-го типа, находившихся на инсу-линотерапии, лечение которых было дополнено препаратом тиазолидинового ряда -пиоглитазо-ном, через 4 месяца было отмечено улучшение эндотелиальной функции на фоне увеличения потокопосредованной вазодилатации [28]. Ис-пользуемые при лечении больных СД ингиби-торы ангиотензинпревращающего фермента (иАПФ), препятствующие разрушению брадики-нина, уменьшают образование ангиотензина II и оказывают прямое влияние на активность NO-продуцирующего фермента.…”
unclassified